Interfacial reactions between Sn-3.5 Ag solder and Ni-W alloy films - Haseeb, A.S. Md. Abdul; Chew, C.S.; Johan, M.R. (Springer, 2011)
Nickel based alloys are currently being investigated in an effort to develop stable barrier films between lead free solder and copper substrate. In this study, interfacial reactions between Ni-W alloy films and Sn-3.5 Ag solder have been investigated. Ni-W alloys films with tungsten content in the range of 5.0-18.0 at. were prepared on copper substrate by electrodeposition in ammonia citrate bath. Solder joints were prepared on the Ni-W coated substrate at a reflow temperature of 250 A degrees C. The solder joint interface was investigated by Cross-sectional scanning electron microscopy, energy dispersive X-ray spectroscopy and electron back scatter diffraction. It has been observed that a Ni(3)Sn(4) layer with faceted morphology formed on the Ni-W alloy film after reflow. The thickness of the bright layer was found to decrease with the increase of tungsten content in the Ni-W film. An additional layer with a bright appearance was also found to form below the Ni(3)Sn(4) layer. The bright layer was identified to be a ternary phase containing Sn, W and Ni. The bright layer is found to be amorphous and is suggested to have formed through solid state amorphization caused by anomalously fast diffusion of Sn into Ni-W film.